@hopehelpsnet sebagai Media Aktivisme dalam Pencegahan Kekerasan Seksual bagi Kalangan Mahasiswa - Amiira Mazaya; Eni Maryani; Ira Mirawati (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
"@hopehelpsnet as a Media for Activism in Preventing Sexual Violence for College Students. This research aims to determine the emergence of Instagram @hopehelpsnet as a medium for activism in preventing sexual violence among students, content management, Instagram account management, and the contributions it provides. This research was conducted using qualitative methods with a case study approach and using interviews, observation, and literature study for data collection. @hopehelpsnet exists as a medium for preventing and handling sexual violence among students. The results of research indicate that @hopehelpsnet first emerged as a provider of sexual violence response and prevention services in various universities in Indonesia after the formation of HopeHelps at Universitas Indonesia. @hopehelpsnet manages content by paying attention to the victim's perspective and trying to educate and mobilize its followers. @hopehelpsnet facilitates its followers by providing complaint services, holding digital discussion rooms, and holding campaigns on the issue of sexual violence. Followers of @hopehelpsnet also said that their knowledge increased after following the @hopehelpsnet account and considered sexual violence an important issue to pay attention to.